Perceptions, Knowledge, Attitudes, and Cervical Cancer Prevention Behavior Among Health and Non-Health Scholar - Solikhah Solikhah; Nahdiya Ayu; Monthida Sangruangake (Kesmas Indonesia, 2023)
Background: Cervical cancer is still a leading cause of death fourth in women in the world and in Indonesia it is the second leading cause of death in women after breast cancer, including in the adolescent group. This study aimed to explore distinguish perception, knowledge, attitude, and cervical cancer prevention among health and non-health scholars in Indonesia. Method: Used an analytical observational design with a cross-sectional approach. The sample in this study were 364 students, consisting of 168 health students and 196 non-health scholars. Data analysis used univariate and bivariate analysis using independent t tests. Results: there are differences in perceptions of cervical cancer prevention between health and non-health students with an average value of 17.34 (2.11) for health students, while for non-health students 16.80 (1.94) with p_value 0.012, including variables knowledge and attitude differences in cervical cancer prevention (in health students the average knowledge = 11.95, 0.95; the average attitude = 21.57, 2.08, while in non-health students the average knowledge = 10.81, 1.06; the average attitude = 20.62, 2.25). The p value for the attitude variable is 0.000 and the knowledge variable is 0.001. Conclusion: there are differences in perceptions, knowledge, and attitudes towards cervical cancer prevention in health and non-health scholars, Indonesia.